Passini, Jean, El camino de Santiago. Itinerarios y núcleos de población, Madrid, Ministerio de Obras Públicas y Transportes, 1993, 248 págs - Martínez Martínez, María (1996)
Fil: Martínez Martínez, María. Universidad de Murcia; España